Psychological pathways of violent and non-violent criminals: an exploration combining network analysis and Bayesian modeling - Wang-Cheng Cen; Cheng-Han Li; Yu-Hao Cui; Wen-Jing Yan (Humanities & Social Sciences Communications)
Abstract Criminal behavior poses a significant threat to social security and public health, with notable psychological differences between violent and non-violent offenders. However, current research lacks a systematic investigation into multidimensional psychological variables and their interactions. This study explored differences in key psychological variables and their interactions between violent and non-violent offenders using network analysis and Bayesian network modeling. Psychological assessments were conducted on 749 male incarcerated individuals (335 violent, 414 non-violent offenders), covering impulsivity, personality traits, mindfulness, reinforcement sensitivity, childhood trauma, moral disengagement, criminal cognition, and risk attitudes. Results indicated mindfulness significantly influenced neuroticism and openness in non-violent offenders but not in violent offenders. Reinforcement sensitivity had a stronger impact on neuroticism among violent offenders. Criminal cognition significantly affected risk-taking via moral disengagement, with different pathways between groups. In non-violent offenders, criminal cognition was negatively moderated by agreeableness and positively related to reinforcement sensitivity; these effects were absent in violent offenders. This study highlights distinct psychological pathways between offender types, suggesting mindfulness-based interventions for non-violent offenders and emotional regulation training for violent offenders, providing practical implications for correctional interventions.